Ethnic/Racial Identity: Fuzzy Categories and Shifting Positions. Issue 1 (May 2018) - Deaux, Kay
Demographic changes and increasing diversity in the United States bring about changes in how people define themselves and how they categorize others. I describe three issues that are relevant to the labeling and self-definition of ethnic groups in U.S. society: (1) the creation and definition of identity categories, (2) the subjectivity of self-definition, and (3) the flexibility of identity expression. In each case, substantial research from social psychology and related disciplines supports a socially constructed definition and use of ethnic categories, wherein identities are subject to the influence of local and national norms and are amenable to change across situations and over time.